The Construction of Gender Roles in Fictional Soap Opera within the Film Joy (2015): A Stuart Hall Reception Analysis (Cinematology: Journal Anthology of Film and Television Studies, 2025)
Although centered on its female audiences, soap operas have long served to legitimize the practice of traditional gender roles. In Joy (2015), soap opera is depicted as one of the medias that construct traditional gender roles while also offering different responses from the characters. This study aims to examine how audience reception influences the meanings constructed by media. By utilizing Stuart Hall’s Encoding/Decoding theory, it analyzes two reading positions represented by the characters Joy and Terry. Terry embodies the dominant reading position by accepting the traditional values, whereas Joy embodies the oppositional reading by rejecting traditional gender roles. The findings suggest that media is not an entirely hegemonic force, as oppositional readers—such as the one presented by Joy—do exist. Ultimately, audiences possess the power to interpret media messages.